Keraphyton gen. nov., a new Late Devonian fern-like plant from Australia - Champreux,Antoine; Meyer-Berthaud,Brigitte; Decombeix,Anne-Laure (PeerJ, 2020)
The first plants related to the ferns are represented by several extinct groups that emerged during the Devonian. Among them, the iridopterids are closely allied to the sphenopsids, a group represented today by the genus Equisetum. They have been documented in Middle to early Late Devonian deposits of Laurussia and the Kazakhstan plate. Their Gondwanan record is poor, with occurrences limited to Venezuela and Morocco. Here we describe a new genus from a late Late Devonian locality of New South Wales. It is represented by a single anatomically preserved large stem characterized by a star-shaped vascular system with protoxylem strands located at rib tips, and by a lack of secondary tissues. Within the first fern-like plants, this stem shares the largest number of characters with iridopterid axes but differs by the pattern of its vascular system. Keraphyton mawsoniae gen. et sp. nov. adds a new record of early fern-like plants in eastern Gondwana. It provides new insights into the anatomical diversity within this key group of plants and supports the distinctiveness of the Australian flora in the latest Devonian.
Keywords: Palaeobotany; Palaeozoic; Early ferns; Gondwana; Australia; Plant anatomy; Iridopteridales